Analysis of Students' Critical Thinking Patterns on Critical Thinking Ability: The Case of Elementary School - Mochamad Guntur; Herisa Hardiyanti Sholeha; Ike Kurniawati; Astuti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2023)
This study aimed at comprehensively analyzing critical thinking patterns in elementary school students through the Grounded Theory method. The design used was a case study. This study involved 25 fourth grade students at Kedung Krisik Elementary School, Cirebon City. Data collection was carried out through critical thinking math test questions; and interviews between researchers and students after completing the test questions. The analysis process was carried out by giving tests to students. The results of this study reveals that students' critical thinking skills in mathematics at the elementary school are divided into three categories, namely CTA 3, CTA 2, and CTA 1. It could be seen that critical thinking skills in mathematics can be improved by practicing working on questions related to mathematics learning, especially in the form of contextual questions. The Watson-Glaser Critical Thinking Appraisal (CTA) critical thinking assessment models could be applied to measure critical thinking skills themselves.